The psychological analysis of humility - Marazaitė, Irena; Kociūnas, Rimantas (Psichologija, 1998)
The article presents the psychological analysis of humility. Different concepts of humility are discussed in the introduction. The article presents the phenomenological study of humility. The authors attempt to define how young people understand and experience humility, try to compare the concept of humility between believers and nonreligious young people, the experience and importance of humility. The subjects define humility as giving precedence to the others (that can be God, other person, life process). This can only be an external action or (and) an inner position and can require to refuse something of one’s own – own wishes, implementation of one’s position, own understanding. Humility is related to reconciliation, experiences of weakness, defeat, inner tension, and dissatisfaction, ranging in intensity.
Keywords: humility; religiousness; phenomenological analysis